Autism Spectrum Disorder Toolkit : For Parents & Caregivers - Townshippers' Association; Autisme Estrie (2024)

Inclusive Mentorship Initiative - Townshippers' Association (2024)
This report provides an overview and evaluation of the 2023-2024 fiscal year ofTownshippers’ Association’s Inclusive Mentorship Initiative (IMI) funded by theSecrétariat aux relations avec les Québécois d’expression anglaise from December 2021to the present.
Keywords: Official Language Minority Community (OLMC)

Inclusive Mentorship Initiative - Townshippers' Association (2024)
This report provides an overview and evaluation of the 2023-2024 fiscal year ofTownshippers’ Association’s Inclusive Mentorship Initiative (IMI) funded by the Secrétariat aux relations avec les Québécois d’expression anglaise from December 2021 to the present. Founded in 1979, Townshippers’ Association is mandated to promote the interests ofthe ESC in the historical Eastern Townships, strengthening the cultural identity of thiscommunity, and encouraging the full participation of the English-speaking population in the community at large. Townshippers’ Association’s projects address heritage andculture, community development, access to health and social services, support for seniors, and youth retention. The Secretariat aux relations avec les Québécois d’expression anglaise is responsible forensuring that the concerns of English-speaking Quebecers are taken into account ingovernment orientations and decisions in collaboration with government ministries and bodies.

Townshippers' Association Annual Report 2023-2024 - Townshippers' Association (2024)

Autism Spectrum Disorder - Townshippers' Association; Autisme Estrie; Dixville Fondation (2024)

Searching for a Work-Life Balance in Your Health and Social Services Career? - Townshippers' Association; Dialogue McGill (2024)

Let's Talk About Grief - Townshippers' Association; Mental Health Estrie (2024)

Townshippers' Association Annual Report 2022-2023 - Townshippers' Association (2023)

Health and Social Services Career Opportunities Training Guide : Eastern Townships Region - Townshippers' Association; Dialogue McGill (2023)

Townshippers' Association Annual Report 2021-2022 - Townshippers' Association (2022)

Townshippers Magazine - Townshippers' Association (2022)

Townshippers Magazine - Townshippers' Association (2022)

A Change in Leadership Ahead for Townshippers’ Association - Townshippers' Association (2021)

Townshippers' Association Reacts to Bill C-32 - Townshippers' Association (2021)

Bill 96, an Act Respecting French, the Official and Common Language of Québec - Townshippers' Association (2021)
Following careful consideration of the proposed changes to existing legislation put forth in Bill 96, Townshippers’ Association is compelled by its mandate to advocate on behalf of the English-speaking community in the historical Eastern Townships to react and raise concerns as they may apply to the diverse communities in our region. While in full agreement that the protection and promotion of the French language and culture is imperative to preserving Quebec’s unique character, the Board of Directors of Townshippers’ Association deplores the government’s attempts to achieve this through an omnibus piece of legislation and its sweeping use of the notwithstanding clause. It is our considered opinion that Bill 96 is not so much a measure designed to raise the status of French within the province and work against its perceived decline in the public sphere, but one aimed at achieving a certain level of social control over the access to, the use, and overall presence of, English within Quebec.
Keywords: Official Language Minority Community (OLMC)

Townshippers' Association Reacts to Bill 96 - Townshippers' Association (2021)

The Official Languages Reform Project - Townshippers' Association (2021)
The February 19th, 2021 position paper put forth by the Canadian Federal Government addressed important issues raised by organizations representative of Canada’ s English-speaking minority language community, including several of those championed by Townshippers’ Association in consultations on the modernization of the Official Language Act (OLA) in 2017, 2018, and 2019 While the Association supports changes designed to improve accountability in its implementation, increase the transparency of federal transfer payments to provinces, and provide increased support for Official Language Minority Communities (OLMC) institutions, it reminds the Canadian Government of its legal responsibility to protect, support and defend the rights of both of its OLMCs, wherever they may be located, and cautions against strengthening the OLA in ways that promote asymmetry between Canada’s Official Languages.
Keywords: Official Language Minority Community (OLMC)

February 2021 Federal Pre-Budget Consultation - Townshippers' Association (2021)
For more than 40 years Townshippers’ Association has been at the forefront of community engagement, pursuing its mission to promote the interests of the English-speaking community in Quebec’s historical Eastern Townships, strengthen its cultural identity, and encourage the full participation of the English-speaking population in the community at large. We work on behalf of more than 40, 000 English-speakers who are spread across a region that is geographically larger than Belgium; stretching from Philipsburg in the west to Megantic in the east, and from Inverness in the north to the U.S. border in the south. This brief will provide essential information regarding factors affecting Official Language Minority Community vitality; recent statistics describing the situation of English-speakers in the Historical Eastern Townships (HET), including preliminary data showing the impacts of the COVID-19 pandemic; and conclude with recommendations for consideration in the development of a new federal budget.
Keywords: Official Language Minority Community (OLMC)

Townshippers' Association : 2020-2021 Annual Report - Townshippers' Association (2021)

Townshippers Magazine - Townshippers' Association (2021)

Townshippers Magazine - Townshippers' Association (2021)

Townshippers’ Association Very Pleased with the Supreme Court of Canada’s Decision re: Minority Language Educational Rights - Townshippers' Association (2020)

2020 English-Speaking Community Award Winners - Townshippers' Association (2020)

Townshippers' Association : 2019-2020 Annual Report - Townshippers' Association (2020)

Townshippers Magazine - Townshippers' Association (2020)

Townshippers Magazine - Townshippers' Association (2020)

Celebrating 40 Years of Community, Culture & Advocacy - Townshippers' Association (2019)

Townships Womxn Celebrate What Makes Them Perfect the Way We Are - Townshippers' Association (2019)

Bill 40 : An Act to Amend Mainly the Education Act With Regard to School Organization and Governance - Townshippers' Association (2019)
For 40 years now Townshippers’ Association has been at the forefront of community engagement, pursuing its mission to promote the interests of the English-speaking community in Quebec’s historical Eastern Townships, strengthen its cultural identity, and encourage the full participation of the English-speaking population in the community at large. We work on behalf of approximately 40,000 English-speakers who are spread across a region that is larger than Belgium in its geography; stretching from Philipsburg in the west to Megantic in the east, and from Inverness in the north to the U.S. border in the south. As indicated in the past in briefs submitted by the association during previous public commission debates around school boards and their governance, Townshipper’s Association fully supports the position that parents, education professionals and community members need to have a greater voice in the governance of schools and the services they provide to both students and the community. This bill, as did similar legislation introduced and subsequently abandoned in the recent past, provides an opportunity to evaluate the importance of these governance structures and propose new and innovative means for improving decision-making processes that will enhance the quality of education for English-speaking minority students, especially in regards to curriculum, pedagogy and student success. However Bill 40 purports to uphold the English-speaking minority language community’s right to the management and control of its educational institutions and maintain a certain level of community involvement, it fails to demonstrate how the structural changes it puts forth will positively impact student success, alleviate costs associated with elections and ensure that democratic processes are upheld through ensuring accuracy in electoral lists.

Bill N°40 : An Act to Amend Mainly the Education Act With Regard to School Organization and Governance - Townshippers' Association (2019)
For 40 years now Townshippers’ Association has been at the forefront of community engagement, pursuing its mission to promote the interests of the English-speaking community in Quebec’s historical Eastern Townships, strengthen its cultural identity, and encourage the full participation of the English speaking population in the community at large. We work on behalf of approximately 40,000 English-speakers who are spread across a region that is larger than Belgium in its geography; stretching from Philipsburg in the west to Megantic in the east, and from Inverness in the north to the U.S. border in the south. As indicated in the past in briefs submitted by the association during previous public commission debates around school boards and their governance, Townshipper’s Association fully supports the position that parents, education professionals and community members need to have a greater voice in the governance of schools and the services they provide to both students and the community.

Townshippers : 40 Years - Townshippers' Association (2019)

Sunshine and Shows Highlight Townshippers’ Festival 2019 - Townshippers' Association (2019)

Townshippers' Association Submits Brief to Bill 21 Consultation - Townshippers' Association (2019)

Bill 21 : An Act Respecting the Laicity of the State - Townshippers' Association (2019)
Following careful consideration of the proposed changes to existing legislation put forth in Bill 21, Townshippers’ Association is compelled to react and highlight issues and concerns as they may apply to Quebec’s diverse English-speaking minority language communities; it is our considered opinion that Bill 21 is not a measure that will enhance the values and personal freedoms already enshrined in both the Canadian and Quebec Charters of Rights and Freedoms. The adoption of this bill and the application of Section 33 of the Canadian Charter of Rights and Freedoms as a work around against any potential charter challenges will only serve to deepen divisions among Quebec residents and increase the isolation of minorities.

Modernization of the Official Languages Act : House of Commons Standing Committee on Official Languages : Townshippers’ Association Opening Remarks - Hunting, Rachel (2019)

Townshippers' Association : 2018-2019 Annual Report - Townshippers' Association (2019)

Townshippers Magazine - Townshippers' Association (2019)

Townshippers Magazine - Townshippers' Association (2019)

Vital Communities and Critical Institutions for the Transmission of English-speaking Quebec’s Cultural, Social, and Historical Identity - Townshippers' Association (2019)
This paper will demonstrate how the role of education in a minority language context is much more comprehensive than simply ensuring academic success or instruction in English and is inherently linked to the transmission of its collective history and culture over generations with particular emphasis on the English-speaking community of Quebec (hereafter referred to as the ESCQ), who are struggling to sustain their vitality.
Keywords: Official Language Minority Community (OLMC)

Modernization of the Official Languages Act - Townshippers' Association (2018)
This brief will explore factors affecting Official Language Minority Community vitality in relation to the Official Languages Act within the context of its modernization and provide recent statistics describing the situation of English-speakers in the Historical Eastern Townships; recommendations for consideration in the updating of this important piece of legislation appear in bold throughout.
Keywords: Official Language Minority Community (OLMC)

Townshippers' Association : Annual Report 2017-2018 - Townshippers' Association (2018)

Townshippers Magazine - Townshippers' Association (2018)

Annual Report 2016/2017 - Townshippers' Association (2017)

English-speaking Seniors : RTS de l'Estrie - CHUS - Townshippers' Association (2016)